Notice of suspicion: procedural significance and influence on the methodology of pre-trial investigation - Volobuyev A. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
he purpose of the article is to determine the essence of the notification of suspicion as an intermediate procedural decision; the possibility of its appeal by the defense; the impact of the notification of suspicion on the methodology of the pre-trial investigation. Methodology. In order to achieve the specified goal, an analysis of national criminal procedural legislation, court practice and scientific publications on the problematic issues of the notification of suspicion and the possibility of appealing it was carried out. Methods. The methods of dialectical, historical, comparative legal, etymological and semantic scientific research were used. Methods of logic (analysis, synthesis, induction, deduction, abstraction) were also used to determine common features and differences between the legal institutions of reporting suspicion and bringing charges, as well as investigative situations. Findings. The conclusions are formulated that the notification of suspicion is an intermediate procedural decision that significantly affects the procedure and methodology of the pre-trial investigation. The notification of suspicion is a legal procedural form of the investigation version, which is subject to verification with the participation of the suspect. The participation of the suspect in verifying this version is a necessary condition for the completeness of the investigation, the realization of his rights and legitimate interests during the pre-trial investigation. After the notification of suspicion is served, its content may subsequently change repeatedly or be replaced by a new suspicion. Therefore, after the expiration of the pre-trial investigation period, there is no point in challenging the initial content of the notification of suspicion on the basis of doubts about the sufficiency of the evidence for this. The object of the appeal (objection) should be only the indictment, which is a final procedural document and is submitted to the court. Originality. For the first time, the essence of a report of suspicion is determined in comparison with the presentation of charges and its impact on the methodology of the pre-trial investigation. Additional arguments are presented regarding the lack of meaning in appealing the initial report of suspicion. Practical significance. The formulated theoretical provisions and practical recommendations are aimed at improving the current criminal procedural legislation, the procedure for drawing up a report of suspicion, and taking into account investigative situations that arise after the interrogation of the suspect.